The Influence of AI Chatbot Usage Frequency and Digital Behavior on Information Ethics Compliance among Indonesia’s Digital Society - Saputry Wahyuni, Haria; Ramdani, Alwan Husni; Rohimakumullah, Muhammad Al Assad (Knowledge Garden: International Journal of Library Studies, 2025)
The rapid advancement of artificial intelligence (AI), particularly generative chatbots such as ChatGPT, has reshaped how individuals access and utilize information in the digital age. However, this development raises critical concerns regarding information ethics, especially as AI tools become increasingly embedded in everyday digital practices. This study investigates the influence of chatbot AI usage frequency and digital behavior on information ethics compliance within Indonesian digital society. Employing a quantitative descriptive approach, the research applies SEM. Data were collected through an online survey of 458 respondents across diverse demographics within one month. The survey instrument consisted of 15 items measuring three constructs: chatbot AI usage frequency, digital behavior, and information ethics compliance. The results indicate that both chatbot usage frequency and digital behavior positively affect information ethics compliance, with digital behavior exerting a stronger direct impact. Furthermore, the interaction between these variables demonstrates the most substantial influence on ethical compliance. While the direct effect of chatbot usage is not statistically significant, its indirect effect through digital behavior is highly significant. These findings underscore that ethical digital behavior functions as a reinforcing mechanism that enhances the responsible use of AI technologies. Overall, the study confirms that adherence to information ethics in the AI era is closely tied to the broader concept of digital citizenship. Promoting digital literacy and ethical awareness is therefore essential to maximize the ethical potential of AI applications. Future research should examine additional mediating variables and develop strategic interventions to foster responsible digital behavior.